The Nixon-in-China Effect: Activism, Imitation, and the Institutionalization of Contentious Practices - Briscoe, Forrest; Safford, Sean (Administrative Science Quarterly, 2008)
This paper seeks to understand how contentious practices spread from initial targets of activism to become accepted by organizations in the mainstream. Using a dataset on the diffusion of domestic partner benefits in the Fortune 500 from 1990 to 2005, we show that widespread adoption among mainstream firms was triggered by the prior adoptions of companies known to resist activism. We also find that employee activist groups within firms played a different role depending on the company's orientation toward activism. Employee groups increased the likelihood of adoption in activism-prone firms, but in mainstream firms, they increased the susceptibility of the firm to prior adoptions by others. These findings support a view of institutionalization as a contested process and suggest an alternative mechanism through which social networks influence that process. Like the effect of Cold-War President Richard Nixon's surprising visit to the People's Republic of China in 1972, which led other countries to open relations with China, adoption of a practice by activism-resistant firms signaled to mainstream firms that an advocated practice had lost its contentiousness. Rather than providing pressure toward conformity, adoption events in a firm's environment can be seen as a cultural resource that supports or undermines the arguments made by proponents of change inside organizations.